The task of the educator as a help to the personal integration oriented to happiness - Ahedo Ruiz, Josu; Millán-Ghisleri, Elda (Revista Complutense de Educación, 2023)
INTRODUCTION: The current article´s main purpose is to show the task of the educator as a help for the personal integration of the pupil whose aim is happiness. To do this the present work leans on the distinction between integral education and personal education. The notion of synderesis is approached as what enables the person to take charge of his own growth and to orient it towards happiness. METHOD. It is a theoretical type study based on a bibliographical revision of the most relevant and updated literature on the topic. OUTCOME AND DISCUSSION. Being character formation a fundamental axis of integral education, it is not enough if we consider the person as a who. The educator task is double and takes his full sense when it helps his pupil to integrate his growth (1) and to orient it towards happiness (2), which is no other thing than giving other the nature´s perfecting acquired through virtue.
Keywords: Character education; integral education; personalized education; happiness